WHAT ARE THE CAUSES AND TYPES OF FARMER TRAUMA? A LITERATURE REVIEW - Maisyaroh, Arista; Prasetya Widianto, Eko; Syaifuddin Kurnianto (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: The application of technology in agricultural mechanization has not been able to prevent or reduce the threat of occupational health problems in farmers. It is necessary to identify the causative or triggering factors. Purpose: Identify the causes and types of injuries experienced by farmers. Review: The method used in this study was a literature review with an electronic database search through Springer Link, Science Direct, Pub-med, and Google Scholar based on the inclusion criteria respondents that were farmers who had experienced work-related trauma and there were interventions in the form of assessment of trauma events in farmers, using the method of a systematic review or analytical retrospective study or a population-based observational study or cross-sectional study, using Indonesian and English, published in 2018-2022. Result: The results of the literature review showed that the causes of trauma due to agriculture were agricultural machinery, hand tools/ manual agricultural tools, farm animals, wild animals, falls, ergonomic positions, and fatigue. At the same time, the types of trauma in farming accidents were soft tissue injuries, concussions, fractures, avulsions, amputations, and infections to death. Conclusion: Work-induced injuries directly affected farmers' lives, so it is necessary to increase knowledge in recognizing the factors causing injuries and management according to the type of injury experienced.